2014
DOI: 10.1117/12.2067283
|View full text |Cite
|
Sign up to set email alerts
|

POLO: a unique dataset to derive the phase angle dependence of the Moon irradiance

Abstract: PLEIADES is a dual Earth observation system composed of two satellites, PLEIADES-1A and PLEIADES-1B, respectively launched at the end of 2011 and 2012. This imagery system, led by CNES, has four spectral bands, blue, green, red and near infrared, with a spatial resolution of 2.8 m and a panchromatic band with a resolution of 0.7 m in vertical viewing. Its swath is about 20 km.In the framework of the PLEIADES radiometric calibration, studies took place in order to determine the calibration precision that could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
3
13
0
Order By: Relevance
“…This phase angle dependence of the ROLO model has been also reported by Lacherade et al (2013Lacherade et al ( , 2014 and Viticchié et al (2013) as well as its asymmetry within the Moon cycle (Lacherade et al, 2013(Lacherade et al, , 2014. Lacherade et al (2014) found a variation up to 5 % with the phase angle between ±90 • , which is the validity range of the ROLO model.…”
Section: Identifying Bias In the Lunar Irradiance Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…This phase angle dependence of the ROLO model has been also reported by Lacherade et al (2013Lacherade et al ( , 2014 and Viticchié et al (2013) as well as its asymmetry within the Moon cycle (Lacherade et al, 2013(Lacherade et al, , 2014. Lacherade et al (2014) found a variation up to 5 % with the phase angle between ±90 • , which is the validity range of the ROLO model.…”
Section: Identifying Bias In the Lunar Irradiance Modelsupporting
confidence: 84%
“…Lacherade et al (2014) found a variation up to 5 % with the phase angle between ±90 • , which is the validity range of the ROLO model. These results are in agreement with the relative differences higher than 4 % found in this study.…”
Section: Identifying Bias In the Lunar Irradiance Modelmentioning
confidence: 61%
See 1 more Smart Citation
“…The residual phase effects determined here for the SeaWiFS lunar observation / ROLO model ratios are consistent with the initial SeaWiFS analysis 8 and are consistent with the PLEIADES observations from the POLO data set. 10 The residual libration effects determined for the SeaWiFS lunar observation / ROLO model ratios are smaller than the libration effects observed for SNPP VIIRS reflective solar bands with wavelengths longer than 412 nm. 11,12 The coherent noise in the SeaWiFS data is high enough that the SeaWiFS data alone are not diagnostic of any residual libration effect in the SeaWiFS / ROLO comparisons.…”
Section: Seawifs Geometry Reanalysis Summarymentioning
confidence: 92%
“…PLEIADES is a French dual instrument Earth observation system, PLEIADES-1A and PLEIADES-1B, each of which is a four-band filter radiometer with a spatial resolution of 2.8 km and swath of 20 km. 10 The OBPG has developed an on-orbit calibration of SNPP VIIRS for ocean color applications. 11 SNPP VIIRS observes the Moon approximately once per month by rolling the spacecraft to achieve a nominal lunar phase angle of −51 • .…”
Section: Introductionmentioning
confidence: 99%